The Role of Organizational Culture in Driving Knowledge Management and Reducing Customer Complaints: A PLS-Sem Study at PT Xyz - Rizki Kurniawan; Aji Baskoro; Dana Indra Sensuse; Nadya Safitri; Sofian Lusa (Eduvest - Journal of Universal Studies, 2025)
High rates of unresolved customer complaints and the absence of structured Key Performance Indicators (KPI) and transparent incentives present significant challenges for PT XYZ, a telecommunications company. These issues undermine employee motivation, operational efficiency, and customer satisfaction, ultimately threatening the company’s profitability and competitive positioning. This study analyzes how Organizational Culture influences Knowledge Management, impacting KPI, System Incentives, and Customer Complaints in a telecommunications company. Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, the findings reveal that Organizational Culture significantly enhances Knowledge Management, which serves as a critical mediator in driving organizational effectiveness. The study highlights the strong and significant relationships between Knowledge Management and internal processes, such as KPI and incentive systems, as well as its moderate impact on reducing customer complaints. The results confirm the mediating role of Knowledge Management in linking Organizational Culture to both operational efficiency and customer satisfaction. These findings emphasize the importance of fostering a strong organizational culture to support knowledge-sharing practices, enabling companies to achieve their strategic goals. Future research could expand on these findings by exploring additional mediating variables or applying the model to other industries.